APPs in sound measurements to gain a school-work experience. (May 2019) - Buongiorno, D; Longo, A; Michelini, M; Pagotto, S; Ricci, D; Santi, L
Abstract: To gain autonomy in studies and work competences, the Italian Ministry of Education introduced a mandatory school-work integration in upper secondary school curriculum. University is one of the possible work area for that students, offering lot of different proposals and experiences. University of Udine and Flaminio Liceum in Vittorio Veneto, in cooperation with University of Salento in Italy, planned to focus on innovation in using ICT for that aim. The research-based formative intervention module of the project phases are the following: choice of a topic (sound), exploration of some suggested mobile APPs for sound measurements, writing of technical reports on APPs by students and relative discussion, the use of City SoundScape APP to monitor landscape from city centre to natural reserve. Problems and learning needs of students have been monitored during the activities to find out the autonomy strategies, paying particular attention to the stimuli and motivational role of the APP use for measurements in developing study and work competences.